2014
DOI: 10.1016/j.ahj.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence of congenital heart defects in Norway 1994-2009—A nationwide study

Abstract: The birth prevalence of CHD declined from around 2005. Specifically, the prevalence of severe CHD was reduced by 3.4% per year from 2004 through 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
116
5
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 22 publications
14
116
5
12
Order By: Relevance
“…The nationwide research project ‘Congenital Heart Defects in Norway’ includes all births in Norway in 1994–2009 6 23 24. This project includes medical data from the following sources: The Medical Birth Registry of Norway is a national health registry managed by The Norwegian Institute of Public Health.…”
Section: Methodsmentioning
confidence: 99%
“…The nationwide research project ‘Congenital Heart Defects in Norway’ includes all births in Norway in 1994–2009 6 23 24. This project includes medical data from the following sources: The Medical Birth Registry of Norway is a national health registry managed by The Norwegian Institute of Public Health.…”
Section: Methodsmentioning
confidence: 99%
“…29 In recent years, congenital heart defects are reportedly less common in the general population, but the magnitude of changes observed among Swedish infants with Down syndrome is unlikely to be explained by factors related to such small general trends. 7,12 Instead, it is plausible that we are observing the consequences of selection. Although most cardiac malformations are treatable, complex malformations may contribute to parents' decision to terminate a pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies from Norway and Canada have demonstrated small declines in the incidence of congenital heart defects over time in the general population. 7,12 Improved diagnostic tools like fetal echocardiography may have led to more pregnancy terminations when severe malformations are diagnosed antenatally. 13 A reduced incidence could also be related to general improvements in reproductive health, for example related to reduced maternal smoking and improved management of morbidities such as diabetes during pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The total population in Norway increased from 4 324 815 to 4 799 252 during this period. CHDs, defined as structural abnormalities of the heart or intrathoracic vessels with functional or potentially functional significance,25 were identified in 11 272 (1.2%) children 12. Of these, the proportion classified as severe CHD was 23.7% (n=2 673) 12 20.…”
Section: Methodsmentioning
confidence: 99%